ANALISIS PERTUMBUHAN DAN KEPADATAN KERANG HIJAU (Perna viridis) PADA TALI GANTUNG KARAMBA APUNG KERANG HIJAU DI LAUT DESA BANYUURIP KECAMATAN UJUNGPANGKAH KABUPATEN GRESIK - Qonita Yasmin Firdaus; Farikhah Farikhah; Nur Maulida Safitri (Universitas Muhammadiyah Gresik, 2023)
Green mussels (Perna viridis) is one of the results of commodity resources mariculture. Green-lipped mussel is one of the marine organisms that have a high nutritional content because clam meat green tea is rich in protein content with content that is equal to 11.84%, the water content of 78.86%, ash 3.60%, fat content low, amounting to 0.70% and also carbohydrates 4.70%. The successful cultivation of green shells should be supported by the ideal environmental conditions so that the activity of the cultivation of which is made environmentally friendly and sustainable. Ujungpangkah subdistrict is one area of the fishery marine has the potential bududaya green-lipped mussels are very abundant. The purpose of this study is to analyze the density, growth rate and hunungan the length of the weight against the green-lipped mussels on the rope hanging karamba floating. Methods of data collection used in this research using purposive random sampling from representatives of the differences in the characteristics at the study site by calculating the density, the rate of daily growth, and the relationship of the length of the weight. The results of research and discussion that researchers get show that the density of the green shells high based on the depth of the strap obtained on the rope part of the bright points that ranged 29802 ind/m2. on the part of the strap in dark points have a value of density, namely 27826 ind/m2. The relationship of the length of the heavy shells of green on the second point (light and dark) is to produce allometrik negative value of b yaitu – of 0.59 and by -0.32 where growth in length is more dominant than the growth of the weight. The dominance of green shells on a light level of the highest on the rope at a depth of 5 by 92,32 % and at the point of the dark level of the dominance of the highest at a depth of 4 that 93,78%. The rate of growth of the daily green shells obtained the highest on a leash to the D ( the Rope is Bright) depth of 4m that is 1,94%/day and the rope to F ( Strap is Dark ) depth of 3m, namely 1.78%/day.